Financialization and Its Impacts on Major Textile Groups in Blumenau and Brusque - Jurgenfeld, Vanessa Follmann (2025)
This article examines the impacts of global financialization on selected large textile companies from Blumenau and Brusque, the main cities of the Itajaí Valley (SC), a well-known hub for the textile sector. The study is based on a theoretical framework covering financialization, transformations in capitalism, and the textile industry, using empirical data from 1990 to 2021. It focuses on the companies' shareholder structures, bankruptcy proceedings, and judicial recovery processes, along with a qualitative analysis that includes the region's economic history and recent regional and global dynamics. This contributes to understanding some of the major changes in the regional development of the Itajaí Valley. The companies analyzed were Buettner, Cremer, Hering, and Teka. Different trajectories were observed: some historic companies in the region either went bankrupt or underwent judicial recovery, while in other cases, financialization ultimately led to the end of family control over the businesses.